Penggunaan Media Boneka Keberagaman Nusantara untuk Meningkatkan Hasil Belajar IPS Kelas IV SD Kanusuys Kotabaru Yogyakarta - Cahya, Yuka Rahmah; Sarkim, Tarsisius (Paedagogie, 2024)
The purpose of this research is to improve student learning outcomes in social studies subjects using the help of Nusantara Dolls media. This type of research is classroom action research which has been carried out in two cycles. In each cycle through 4 stages, namely planning, action, observation and reflection. This research was conducted at Kanisius Elementary School, Kota Baru, with the research subject being fourth grade students at Kanisius Elementary School, Kota Baru, with a total of 20 students. Data collection tools using observation and tests. The results of the study show that applying Nusantara Dolls media in social studies learning can increase social studies learning activities and outcomes in learning. This can be proven from the results of social studies learning outcomes, namely an increase in learning outcomes can affect learning outcomes as evidenced by the acquisition of pre-cycle action results with an average of 55.5 to increase in cycle 1 to 63.4 and to increase in cycle 2 to 75.8